Pengembangan Knowledge Management System Pada Perusahaan Multifinance: Studi Kasus Pada Bess Finance Cabang Slawi - - STMIK Nusa Mandiri Jakarta, Husni Faqih (Universitas Bina Sarana Informatika, 2015)
ABSTRAK - Economic growth is now growing rapidly, so it is necessary to finance companies lending capital which resulted in many similar companies so that competition among finance companies are very strict. Accurate and useful information to form a knowledge. Knowledge of the organization can make the organization aware of its existence and the purpose of finding a way to achieve that goal. Currently there are many finance companies that have not implemented knowledge management (knowledge management) well. Yet in the midst of intense competition needed a strong organization. The organization will be weakened if there is tacit knowledge that comes from expert personnel lost due to the exit of the organization's personnel. It is very dangerous for the survival of the organization. So, we need a container of Knowledge Management System to manage the existing knowledge so that knowledge of the organization will continue to evolve. This study discusses the development of Knowledge Management System to process consumer financing in BESS Finance Branch Slawi. The study began with a search for data, information, and knowledge that exist in the company that would be known knowledge assets owned company that later knowledge will continue to be developed using KMS. To obtain the Knowledge Management process analysis used contingency factor by holding a Focus Group Discussion (FGD) and to determine the architecture of KMS architecture Tiwana Amrit (2000). Results from this study produced a model Knowledge Management System to process consumer financing. Kata kunci: Knowledge Management System, KMS, Multifinance